ANALISIS KENDALA DAN SOLUSI PEMBELAJARAN AGAMA ISLAM DENGAN PENDEKATAN DARING DI SMPN 9 MALANG - Silvia Umaya Sari; Anwar Sa’dullah; Arief Ardiansyah (VICRATINA, 2021)
Learning media available online are very diverse and constantly evolving. The existence of these media is very helpful for teachers in the learning process in the classroom without being preoccupied with the activities of making the media itself. Teachers can take advantage of teaching video applications that display the teacher's face so that it is more effective in delivering information to students than just narrating information. Utilization of the messaging feature can also be used as a means of discussion. Teachers can also use learning media as a means of evaluating the assessment at the end of the lesson. In addition to having the advantages of using social media in online learning, it also has disadvantages. This study aims to (1) describe the process of learning Islam with an online approach at SMPN 9 Malang (2) describe the obstacles faced by Islamic Religious Education teachers in learning using the online method. (3) describe the efforts that are used as solutions related to obstacles in learning using online methods at SMPN 9 Malang.